Probabilitas Pelaksanaan Hak Angket Terhadap Pemilihan Umum di Indonesia - Hasanah, Nuranida; Setiadi, Wicipto (JURNAL USM LAW REVIEW, 2024)
This study aims to analyze the role of the right of inquiry in the Parliament's oversight function juridically and the probability of using the right of inquiry in elections in Indonesia. The demand for stronger election oversight can be seen from the survey results, which stated that 62.2% of respondents agreed to use the right of inquiry to investigate allegations of election fraud. However, the House of Representatives' right of inquiry proposal has generated pros and cons from various circles. The existence of several shortcomings in the regulation of the right of inquiry has the potential to cause legal uncertainty and new legal problems. Therefore, research is needed to determine the juridical position of the right of inquiry and the probability of its use in future elections. This normative law research uses statutory and conceptual approaches. Based on the research conducted, it is known that based on their duties and authorities, the independent institutions of KPU and Bawaslu are included in the executive branch of power so that they are not immune from the right of inquiry of the House of Representatives. The right of inquiry for elections can be exercised by improving the regulation of the right of inquiry to be more specific. Investigations in the right of inquiry include constitutional actions whose results are in the form of proposals regarding the formulation of policies regarding elections (both forming and improving laws) or as one of the supporting materials in the evidence of election disputes at the Constitutional Court. This study focuses on the probability of Parliament using its authority to conduct investigations in elections in Indonesia and its use in the constitutional system. Penelitian ini bertujuan untuk menganalisis mengenai penggunaan hak angket DPR dalam Tata Negara Indonesia serta probabilitas penggunaan hak angket dalam Pemilihan Umum (Pemilu) di Indonesia. Indikasi lemahnya pengawasan dalam pemilihan umum menjadi latar belakang usulan penggunaan hak angket DPR guna menyelidiki dugaan pelanggaran pemilu yang melibatkan berbagai pihak. Dalam hal pemilu, penggunaan hak angket DPR menimbulkan pro dan kontra dari berbagai kalangan. Oleh karena itu, diperlukanlah penelitian guna mengetahui kedudukan hak angket dalam tata negara Indonesia serta probabilitas penggunaannya dalam pemilihan umum (pemilu) ke depannya. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Berdasarkan penelitian yang telah dilakukan diketahui bahwa penggunaan hak angket terhadap KPU maupun Bawaslu bisa dilakukan meskipun merupakan lembaga independen dengan tujuan optimalisasi pelaksanaan fungsi pengawasan pemilu. Penyelidikan dalam hak angket termasuk tindakan ketatanegaraan yang hasilnya dapat berupa usulan mengenai perumusan kebijakan mengenai pemilu (baik membentuk maupun memperbaiki undang-undang) ataupun sebagai salah satu bahan pendukung dalam bukti sengketa pemilu di MK. Probabilitas DPR menggunakan kewenangannya untuk melakukan penyidikan dalam Pemilu di Indonesia dan penggunaannya dalam sistem ketatanegaraan merupakan fokus penelitian ini.